THE INFLUENCE OF RISK FACTORS ON THE DEVELOPMENT OF BIRTH DEFECTS AMONG NEWBORNS IN LVIV REGION (UKRAINE) IN 2002–2022 (PART 2) - Hnateiko, Oleh; Kitsera, Nataliya; Henyk-Berezovska, Sofiya; Lukyanenko, Nataliia; Lototska-Savchak, Oksana; Hruzyntseva, Nataliya (Праці Наукового товариства імені Шевченка. Медичні науки, 2024)
Introduction. Birth defects (BDs) are an essential public health issue in children; the identification of probable risk factors should be a priority for the healthcare system. Objectives: This study aimed to determine the probable risk factors for “model” BDs in newborns. Methods. We collected and analyzed clinical-epidemiological and medical-statistic data from the primary records of children with BDs born in 2002–2022 using the “case-control” method, filling out the registration cards in maternity hospitals of Lviv Region (Ukraine). Results. There were 1,279 healthy newborns’ cards and 1,286 cards of newborns with BDs filled out. No significant difference was found in terms of body weight, height, head circumference, and chest circumference (p>0.05) among children with BDs and the control group. The age of mothers with children affected by BD was 27.3±6.1 years and had no statistically significant difference from the age of mothers of children in the control group - 25.6±7.2 years (p>0.05). Mothers who gave birth to children with BDs used drugs in the preconception period [OR=2.46; 95% CI: 1.75; 3.44] and the first trimester of pregnancy [OR=4.76; 95% CI: 3.18; 7.14] significantly more often (p<0.05) compared to mothers in the control group. Pre-pregnancy preparations were adequately conducted by 278 (21.6%) women who gave birth to children with BDs, which was statistically different from 563 (44%) women in the control group (p<0.05) [OR=2.85; 95% CI: 2.39; 3.39]. Conclusions. More efforts are necessary to identify drug safety issues during pregnancy and to improve the current information system for clinical practice.